2022
DOI: 10.3389/fnins.2022.1048565
|View full text |Cite
|
Sign up to set email alerts
|

Mapping trends and hotspot regarding gastrointestinal microbiome and neuroscience: A bibliometric analysis of global research (2002–2022)

Abstract: BackgroundScholars have long understood that gastrointestinal microorganisms are intimately related to human disorders. The literature on research involving the gut microbiome and neuroscience is emerging. This study exposed the connections between gut microbiota and neuroscience methodically and intuitively using bibliometrics and visualization. This study’s objectives were to summarize the knowledge structure and identify emerging trends and potential hotspots in this field.Materials and methodsOn October 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 132 publications
(137 reference statements)
1
2
0
Order By: Relevance
“…Researchers may profit from their country’s economic success, which may provide financial assistance and travel chances. This finding is consistent with past studies that have shown the United States to be the top in research productivity[ 41 - 43 ]. Nonetheless, it is critical to remember that research productivity is only one component of scientific research.…”
Section: Discussionsupporting
confidence: 93%
“…Researchers may profit from their country’s economic success, which may provide financial assistance and travel chances. This finding is consistent with past studies that have shown the United States to be the top in research productivity[ 41 - 43 ]. Nonetheless, it is critical to remember that research productivity is only one component of scientific research.…”
Section: Discussionsupporting
confidence: 93%
“…Data collection WOS core collection database is one of the most comprehensive, systematic and authoritative databases, containing over 13000 internationally recognized in uential academic journals that have been widely used for bibliometric analysis [19,20]. We referred to previous publications and developed search strategies related to oxidative stress and ischemic stroke (Table S2) [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis is a powerful technique that can be applied to assess any particular research topic, predict emerging patterns, and reveal the research frontiers in a scientific field (Deng et al, 2022). Traditional literature reviews and systematic reviews cannot provide multiple perspectives in such an intuitive way as this approach (Yang et al, 2022). This method has been applied to analyze the hotspots of diabetes and its complications, assisting in the development of further research on disease prevention and treatment (Dehghanbanadaki et al, 2022;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%